Association of serum uric acid-to-high-density lipoprotein cholesterol ratio with non-alcoholic fatty liver disease in American adults: a population-based analysis - Xie, Yilian; Huang, Kai; Zhang, Xiangyu; Wu, Zhouxiao; Wu, Yiyi; Chu, Jinguo; Kong, Weiliang; Qian, Guoqing (Frontiers in Medicine, 2023)
Objective: Non-invasive disease indicators are currently limited and need further research due to the increased non-alcoholic fatty liver disease (NAFLD) prevalence worldwide. The serum uric acid to high-density lipoprotein cholesterol ratio (UHR) has been recognized as a novel inflammatory and metabolic marker. Herein, we explored the correlation between UHR and the risk of NAFLD in depth. Methods: Typically, 3766 participants were included in our survey and the National Health and Nutrition Examination Survey (NHANES) 2017–2018 cycle provided the cross-sectional study population. Weighted multivariable logistic regression and multivariate linear regression analysis were performed to assess the association between UHR and the odds of NAFLD and liver steatosis and fibrosis severity, respectively. Moreover, we explored the non-linear relationship between UHR and NAFLD by the generalized additive model. Results: NAFLD probabilities were statistically demonstrated to be positively correlated with UHR (OR = 1.331 per SD increase, 95%CI: 1.100,1.611). The positive connection of UHR with NAFLD risk persisted significantly in women but not in men in subgroup analyses stratified by gender. The non-linear relationship analysis demonstrated that a UHR between approximately 20% and 30% suggested a saturation effect of NAFLD risk. Furthermore, a dramatically positive correlation was found between UHR and hepatic steatosis severity but not fibrosis. Finally, the receiver operating characteristic analysis suggested that UHR had a better predictive value for NAFLD than either serum uric acid (sUA) or high-density lipoprotein cholesterol (HDL) alone [UHR (Area Under Curve): 0.6910; 95% CI: 0.6737-0.7083; P < 0.0001]. Conclusions: Our investigation revealed that elevated UHR level was independently related to an increased NAFLD risk and the severity of liver steatosis in American individuals. The correlation differed according to sex. This non-invasive indicator may enhance the capacity to predict the onset of NAFLD and maybe uncover alternative therapeutic interventional targets.